Spectrum and frequencies of non GJB2 gene mutations in Czech patients with early non-syndromic hearing loss detected by gene panel NGS and whole-exome sequencing - Safka Brozkova, Dana; Poisson Marková, Simona; Mészárosová, Anna Uhrová; Jenčík, Ján; Čejnová, Vlasta; Čada, Zdeněk; Laštůvková, Jana; Rašková, Dagmar; Seeman, Pavel (Clinical genetics, 2020)
Non-syndromic autosomal recessive hearing loss is an extremely heterogeneous disease caused by mutations in more than 80 genes. We examined Czech patients with early/prelingual non-syndromic, presumably genetic hearing loss (NSHL) without known cause after GJB2 gene testing. Four hundred and twenty-one unrelated patients were examined for STRC gene deletions with quantitative comparative fluorescent PCR (QCF PCR), 197 unrelated patients with next-generation sequencing by custom-designed NSHL gene panels and 19 patients with whole-exome sequencing (WES). Combining all methods, we discovered the cause of the disease in 54 patients. The most frequent type of NSHL was DFNB16 (STRC), which was detected in 22 patients, almost half of the clarified patients. Other biallelic pathogenic mutations were detected in the genes: MYO15A, LOXHD1, TMPRSS3 (each gene was responsible for five clarified patients, CDH23 (four clarified patients), OTOG and OTOF (each gene was responsible for two clarified patients). Other genes (AIFM1, CABP2, DIAPH1, PTPRQ, RDX, SLC26A4, TBC1D24, TECTA, TMC1) that explained the cause of hearing impairment were further detected in only one patient for each gene. STRC gene mutations, mainly deletions remain the most frequent NSHL cause after mutations in the GJB2.
Keywords: mezibuněčné signální peptidy a proteiny; Female; nádorové proteiny; vysoce účinné nukleotidové sekvenování; genetická predispozice k nemoci; nedoslýchavost; Membrane Proteins; Adolescent; Neoplasm Proteins; Serine Endopeptidases; konexin 26; mužské pohlaví; mutace; sekvenování exomu; transportní proteiny; mladý dospělý; Genetic Predisposition to Disease; Humans; dospělí; High-Throughput Nucleotide Sequencing; Deafness; hluchota; Czech Republic; Cadherins; membránové glykoproteiny; Membrane Glycoproteins; lidé; serinové endopeptidasy; kadheriny; Carrier Proteins; ženské pohlaví; Child; Česká republika; membránové proteiny; Connexin 26; myosiny; Hearing Loss; Mutation; Young Adult; dítě; Adult; Intercellular Signaling Peptides and Proteins; Exome Sequencing; Male; mladiství; Myosins